1363 Spiralling into control: the impact of a structured programme and dedicated education-based fellows on local education feedback. (17th August 2022) - Milton, Joanne; Carter, Benjamin
Abstract : Aims: The RCPCH trainee charter enshrines the importance of regular, high quality teaching in the development of capable, well-rounded paediatric clinicians. Poor GMC trainee feedback pertaining to the local teaching programme at St Richard's Hospital in 2019 led to the development of two posts: education fellow (EF) and simulation fellow (SF). These hybrid posts combined part time clinical middle grade responsibilities with dedicated time to formalise, rejuvenate and restructure the local educational programme, which had previously been organised on an ad-hoc basis. The key objectives were: 1. To formalise teaching timetable and to trial a structured, curriculum mapped, multifaceted approach. 2. For the paediatric department at St Richards to deliver high quality, regular teaching with the new fellows taking overall responsibility for organisation of teaching rota. 3. For regular simulation sessions and debriefing to be incorporated into training Methods: 20 core topics for weekly themes were identified from the RCPCH and GP trainee curricula. Core educational events including SHO peer teaching, consultant led session, journal club and simulation scenario all mapped to the weekly theme and delivered consistently wherever safe staffing and emergency cover allowed. Both fellows were enrolled in PGCert programmes (EF - Clinical Education, SF – Simulation in Clinical Practice) at Brighton and Sussex Medical School to enhance their skill base and ability to deliver upon the post objectives. The educational theory covered within these programmes was directly applied to the structure of the new education programme – principally the concepts of constructivism and spiral learning through the weekly themed approach. Infrastructure was created to assist both rollout and sustainability of the scheme, including: weekly education summary and calendar email, simulation library and presentation archive. The outcomes for the education programme were evaluated via a departmental questionnaire, GMC survey results and local faculty group feedback. Results: GMC National Trainee Survey showed a satisfaction score in 2019 of 55.95 (lowest quartile), in 2021 this significantly improved to 74.44. Local questionnaire demonstrated 83.3% of junior doctors rated departmental teaching as excellent overall, with 66.7% rating topic of the week as helpful and 100% reporting curriculum needs met. 66.6% of trainees reported that they found the weekly theme helpful in preparing teaching sessions, with the remaining 33.3% finding it occasionally difficult to think of an appropriate subject. The majority of respondents rated all teaching formats as useful or very useful. Informal qualitative feedback from the team was largely positive. Conclusion: The presence of fellows with dedicated educational administrative time was instrumental in embedding a new educational theory-based system within the department, which led to significant improvement in satisfaction ratings. This has supported a sustainable change to ensure key learning outcomes are achieved throughout the department. Education based fellow posts provide high quality personal professional and educational development as well as leadership and organisational experience within a critical realm of paediatric medical training, whilst providing a clear framework to best meet the educational needs of the whole team as the trainee charter recommends.